Associations between peripheral androgens and cortisol in infertile women. Issue 158 (April 2016) - Gleicher, Norbert; Seier, Kenneth; Kushnir, Vitaly A.; Weghofer, Andrea; Wu, Yan-Guang; Wang, Qi; Albertini, David F.; Barad, David H.
Highlights: Sharing a primordium, adrenals and ovarian also share reproductive functions. This included androgen production and, therefore, folliculogenesis. AI in women of reproductive age should lead to suspicion of LFOR. Low androgen precursors and/or T in LFOR should lead to suspicion of AI. Abstract: Testosterone has in recent years been proven essential for normal growth and maturation of small growing follicles. Concomitantly, low functional ovarian reserve (LFOR), characterized by a small growing follicle pool, has been associated with low testosterone levels, which can be of ovarian and/or adrenal origin. In this study we, therefore, investigated whether peripheral sex steroid precursors and testosterone levels potentially reflect on adrenal function. In a retrospective cohort study of 355 consecutive infertile women, who presented to an academically affiliated fertility center in New York City, we investigated in a series of statistical models whether low peripheral sex steroid precursors and testosterone are associated with peripheral cortisol (C) levels, reflecting adrenal function. To determine potential correlations, we investigated the dehydroepiandrosterone (DHEA), DHEA sulfate (DHEAS), androstenedione (AD), total testosterone (TT), free testosterone (FT); sex hormone binding globulin (SHBG), anti-Müllerian hormone (AMH), thyroid stimulating hormone (TSH) and C in a series of multivariate and logistic regression analyses, utilizing C either as a continuous variable or with cut off <5.0 μg/dL, and TT only as a continuous variable. Practically all models demonstrated significant predictability of peripheral sex hormone precursors for C levels, with DHEA demonstrating the strongest and most consistent predictability as an individual parameter and as part of the DHEAS/DHEA ratio. We conclude that in infertile women peripheral sex hormone precursors, especially DHEA, reflect C levels and, therefore, adrenal function. In infertile women, at all ages low levels of sex hormone precursors, therefore, should be considered indications for further adrenal assessments.